Coding and Cryptology Third International Workshop, IWCC 2011, Qingdao, China, May 30-June 3, 2011. Proceedings - Chee, Yeow Meng.; Guo, Zhenbo; Ling, San.; Shao, Fengjing; Tang, Yuansheng; Wang, Huaxiong; Xing, Chaoping; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Third International Workshop on Coding and Cryptology, IWCC 2011, held in Qingdao, China, May 30-June 3, 2011. The 19 revised full technical papers are contributed by the invited speakers of the workshop. The papers were carefully reviewed and cover a broad range of foundational and methodological as well as applicative issues in coding and cryptology, as well as related areas such as combinatorics.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Coding theory; Computational complexity; Coding theory -- Congresses; Cryptography -- Congresses; Electronic books